Preventive Maintenance Strategies to Increase Industrial Machine Life - Suprapto, Muhammad (Journal of Renewable Engineering, 2025)
In modern industries that increasingly rely on machines and automation systems, efficient maintenance is key to maintaining production continuity and avoiding losses due to unscheduled downtime. Preventive maintenance has emerged as a more effective solution compared to the corrective maintenance approach, which is reactive. This study discusses the urgency of implementing preventive maintenance in improving machine reliability, extending equipment life, and reducing long-term costs. The use of advanced technologies such as the Internet of Things (IoT), Computerized Maintenance Management Systems (CMMS), and predictive analytics can optimize preventive maintenance by detecting potential failures early, thereby minimizing downtime by up to 50%. However, the effectiveness of this strategy is highly dependent on the readiness of the digital infrastructure and the competence of the human resources (HR) who manage the technology. Without the integration of historical data, real-time monitoring systems, and adequate training, the implementation of preventive maintenance is at risk of being less than optimal. Therefore, the development of a technology-based preventive maintenance strategy must be accompanied by increased technical and managerial capacity, as well as organizational readiness to adapt to digital change. This research shows that a structured, data-driven preventive approach can support operational efficiency, strengthen competitiveness, and support industry sustainability.